1984
DOI: 10.1002/ajpa.1330650405
|View full text |Cite
|
Sign up to set email alerts
|

Reduced tooth size in 45,X (Turner syndrome) females

Abstract: Mean values and variances of deciduous and permanent tooth dimensions were compared between 121 45,X (Turner syndrome) females and 171 control subjects to clarify the role of the X chromosome on dental development. Although deciduous molars tended to be smaller than normal in 45,X females, there was no evidence of a reduction in tooth size for deciduous anterior teeth. In the permanent dentition, all mesiodistal dimensions were significantly smaller in 45,X females but only some of the buccolingual dimensions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
1
2

Year Published

1985
1985
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 11 publications
(11 reference statements)
4
36
1
2
Order By: Relevance
“…Disruptions in these genes result in enamel mineralization pathologies such as amelogenesis imperfecta (AI) (110). Abnormalities in actual enamel thickness are associated with variations in the number of sex chromosomes (111)(112)(113)(114)(115). However, many versions of AI show inheritance patterns consistent with the localization of major loci on autosomes (116)(117)(118)(119)(120) and nonpathological primate enamel thickness variation is not sexually dimorphic (44,115,121).…”
Section: An Integrative Approachmentioning
confidence: 99%
“…Disruptions in these genes result in enamel mineralization pathologies such as amelogenesis imperfecta (AI) (110). Abnormalities in actual enamel thickness are associated with variations in the number of sex chromosomes (111)(112)(113)(114)(115). However, many versions of AI show inheritance patterns consistent with the localization of major loci on autosomes (116)(117)(118)(119)(120) and nonpathological primate enamel thickness variation is not sexually dimorphic (44,115,121).…”
Section: An Integrative Approachmentioning
confidence: 99%
“…The studies on normal males and females (Garn andRohman 1962, Alvesalo 1971), and on individuals with different kinds of sexchromosome abnormalities (Filipson, Lindsten and Almquist 1965, Alvesalo, Osborne and Kari 1975, Alvesalo and Karl 1977, Alvesalo and de la Chapelle 1979, Alvesalo and Portin 1980, Alvesalo and Varrela 1980, Karl, Alvesalo and Manninen 1980, Alvesalo and de la ChapeUe 1981, Alvesalo and Tammisalo 1981, Townsend, Jensen and Alvesalo 1984, Townsend and Alvesalo 1985, have suggested the presence of genetic factors in the X and Y chromosomes which influence tooth-crown growth and development. With regard to the way these factors exert their influence, the results of the report on enamel thickness in teeth of 45,X females (Alvesalo and Tammisalo 1981) suggested that within the Y chromosome there are at least two factors which influence growth: the first influences amelogenesis one way or another, the other may exert its effect by promoting cell proliferation during odontogenesis.…”
Section: Introductionmentioning
confidence: 96%
“…Measurements of tooth crown size obtained from dental models have shown that the teeth of 47,XYY males and 47,XXY males are generally larger than those of normal males, while 45,X and 45,X/46,XX females have smaller teeth than do normal females (Filipsson et al, 1965;Alvesalo et at., 1975; Alvesalo and Kari, 1977;Alvesalo and Portin, 1980;Kari et al, 1980;Townsend et al, 1984;Alvesalo, 1985;Townsend and Alvesalo, 1985a, b;Townsend et al, 1988;Varrela et al, 1988). Females with complete testicular-feminizing syndrome (46,XY females) have teeth with sizes similar to those of normal males (Alvesalo and Varrela, 1980).…”
mentioning
confidence: 92%